The Condition of Moral Theory in Modern Age; An Analisys of Charles Taylor's Theory of Authenticity Ethics - Hasan Boozhmehrani (اخلاق وحیانی)
There are two turning points. The first one finds its roots in Descartes revolution of philosophy and epistemology. the historical appearance and expansion of Descartes philosophy was equal to the decline of the Middle Ages's worldview and the bith of human subject and overall changes in debates and subjects of different scientific branches. And according to the ideas of the modern age such as liberalism, democracy, human rights, scientific rationality and legalism new social organizations and relationships were stablished. According to it, the understanding of moral rules and judgements went under exceptional changes. The second tuning point took place in the middle of the twentieth century. according to the contemporary Epistemology, many of the Enlightenment ideas were tuned into legends and illusions. Charles Taylor,bieleves that the expansion of Descartes Naturalist Epistemology was lead to overcomming the Relativist, Atomistic and Nihilist interpretaion of moral act and being misleaded from the ideal of modern Moral Authenticity. Taylor's theory of Moral Authenticity, along side giving a defence of the necessity of self-actualization and self-honesty trys to present a richer understanding of life in the framework of inevitable moral goods. It seems that Tylor's moral theory to return to Romanticism tradition in order to revitalize the moral excellence is Insufficient and is more religious Virtue -oriented rather than Modern Authenticity ideal. Also seeking the help of different sources like: communitarian relations, cultural- lingual traditions, Romanticism and Rousseau's inwardness to explaining and justifying the Moral Authenticity, has made his theory even more ambiguous.